Effect of antihypertensive therapy on the life quality of patients with hypertensive encephalopathy - O. V. Gavrilyuk; V. V. Mashin; L. A. Belova; V. I. Gorbunov; V. I. Ruzov; L. V. Nazina (Бюллетень сибирской медицины)
To analyze patients with hypertensive encephalopathy (HE) in the course of antihypertensive therapy (AT) clinical psychological and neurological characteristics in dynamics of 6 months after the first screening were estimated. 107 patients with HE of I—III stages and 30 controls matched for age and sex were examined. The clinical, ultrasonic diagnostics and quality of life (QL) index were applied. In the process of HE development and progression decreases of the physical and psychological constituents of health were shown, pain barrier was decreased. The QL analysis shown that in the process of AT in dynamics the physical and psychological constituents of health increase.